Pengembangan Prototype Water Flow Meter Berbasis IOT Dengan Sistem Monitoring Menggunakan ESP 8266 Pada Pipa Di Unit Water Treatment Plant PT. Perkebunan Nusantara II PKS Sawit Hulu - Hermansyah, Hermansyah; Silitonga, Nelson (CV. IRA PUBLISHING, 2023)
This research aims to develop a prototype IoT-based water flow sensor to monitor water flow in real-time. This prototype uses micro-scale water flow sensor technology that is sensitive and efficient in energy use. It combines it with an IoT-based wireless communication module to send water flow data to the server. The data obtained from these sensors can then be accessed and analyzed via the web or mobile application. This prototype also incorporates a monitoring element, where users can monitor water flow remotely via a mobile or web application.